Close encounters of the third kind [videorecording (Blu-Ray)] - Spielberg, Steven, 1946-; Dreyfuss, Richard; Garr, Teri, 1944-; Dillon, Melinda, 1939- (Columbia Pictures Industries, 2017)
A man becomes obsessed with aliens after having a close encounter, and a woman searches for the visitors who took her son. Their searches eventually lead them to each other and a government project.